THE EFFECT OF AUTOGENIC RELAXATION THERAPY COMBINED WITH MOZART MUSIC ON BLOOD PRESSURE REDUCTION IN HYPERTENSIVE PATIENTS: A QUASI-EXPERIMENTAL STUDY - Ropei, Oop; Tamin, Sukmawati; Kumala, Tria Firza; Fitri, Rita (DPW PPNI Provinsi Jawa Barat, 2025)
Background: Hypertension remains a leading global health concern in both developed and developing countries. In Indonesia, the prevalence of hypertension reached 35.9% in West Java in 2018. Beyond pharmacological approaches, complementary therapies such as autogenic relaxation enhanced with classical music have shown promise in managing blood pressure. Objective: This study aimed to examine the effect of autogenic relaxation therapy using Mozart music on systolic and diastolic blood pressure among patients with primary hypertension. Methods: A pre-experimental one-group pretest-posttest design was employed. The study involved 36 participants with primary hypertension, selected through non-probability purposive sampling. The intervention consisted of autogenic relaxation therapy accompanied by Mozart music for 15 to 20 minutes per session, administered over three consecutive days. Data were analyzed using univariate and bivariate statistical methods. The Wilcoxon signed-rank test was used to assess changes in systolic and diastolic blood pressure before and after the intervention. Results: The mean systolic and diastolic blood pressure before the intervention were 144.17 mmHg and 90.56 mmHg, respectively. After the intervention, mean systolic pressure decreased to 126.67 mmHg, and diastolic pressure to 82.22 mmHg. A significant difference was observed in both systolic and diastolic readings (p < 0.001), indicating the effectiveness of the intervention. Conclusion: Autogenic relaxation therapy using Mozart music demonstrated a significant reduction in blood pressure and may serve as an effective complementary therapy in the management of hypertension.